Antinuclear Antibodies in Systemic Lupus Erythematous - Their Complex Role and Clinical Significance in Diagnosis - Natalia Kucy; Paula Kula; Alicja Kotula; Olga Grelewicz; Adrianna Czachor; Elwira Servaas; Adam Juśkiewicz; Mateusz Haber (Nicolaus Copernicus University in Toruń, 2024)
Antinuclear antibodies (ANA) are a wide group of proteins directed against autologous cellular components, primarily nucleic acids and histones. Their levels are assessed using immunofluorescence on Hep-2 cells or a solid-phase ANA screening immunoassay to subsequently obtain titer value with positive cut-point of ≥1:80. Studies show that ANA can be found in 13% of general population, but typically they are associated with autoimmune conditions and inflammatory connective tissue diseases for example: systemic lupus erythematosus (SLE), sjögren's syndrome, rheumatoid arthritis, mixed connective tissue disease, juvenile idiopathic arthritis, systemic sclerosis, inflammatory myopathies. ANA detection is especially important for SLE, where 2 antibody types - anti-Sm and anti-dsDNA - serve as an entry diagnostic criterion. With increasing patient screening for those antibodies, it is important to determine that alone, positive ANA assays cannot confirm nor deny any disease and to classify their presence as a marker of a disease it is required to satisfy additional additive criteria approved in 2019 by European League Against Rheumatism/American College of Rheumatology. SLE diagnosis can be made when patient collects 10 points from clinical or immunologic domains described by EULAR/ACR, which makes SLE diagnosis challenging and therefore, describing the guidelines is vital to remain cautious about overestimation of the position positive ANA values hold in clinical practice. In conclusion the positive ANA test may be a basis for diagnosis, when additional symptoms occur, but alone does not hold any diagnostic significance and may lead to unnecessary stress for patient.